Physiologically based pharmacokinetic modeling of polyethylene glycol-coated polyacrylamide nanoparticles in rats. Issue 1 (August 2014) - Li, Dingsheng; Johanson, Gunnar; Emond, Claude; Carlander, Ulrika; Philbert, Martin; Jolliet, Olivier
Abstract Nanoparticles' health risks depend on their biodistribution in the body. Phagocytosis may greatly affect this distribution but has not yet explicitly accounted for in whole body pharmacokinetic models. Here, we present a physiologically based pharmacokinetic model that includes phagocytosis of nanoparticles to explore the biodistribution of intravenously injected polyethylene glycol-coated polyacrylamide nanoparticles in rats. The model explains 97% of the observed variation in nanoparticles amounts across organs. According to the model, phagocytizing cells quickly capture nanoparticles until their saturation and thereby constitute a major reservoir in richly perfused organs (spleen, liver, bone marrow, lungs, heart and kidneys), storing 83% of the nanoparticles found in these organs 120 h after injection. Key determinants of the nanoparticles biodistribution are the uptake capacities of phagocytizing cells in organs, the partitioning between tissue and blood, and the permeability between capillary blood and tissues. This framework can be extended to other types of nanoparticles by adapting these determinants.